2020
DOI: 10.1590/0104-9224/si25.26
|View full text |Cite
|
Sign up to set email alerts
|

The Microstructure and Mechanical Behavior of TRIP 800 and DP 1000 Steels Welded by Electron Beam Welding Method

Abstract: TRIP 800 steel and DP 1000 steel welded by using the electron beam welding (EBW) method were investigated in this study. Martensite was a dominant phase at the fusion zone (FZ) of both steels. In addition, bainite and austenite were observed in the FZ of TRIP 800. The hardness of FZ and heat affected zone (HAZ) of both steels were higher than their base metals. The hardness of FZ of the TRIP 800 joinings was higher than the FZ of DP 1000. Ductility and tensile strength decreased at both of the joinings. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The average tensile strength of the welded joints is 925 MPa under different welding parameters. The tensile strength of the dual-phase steel welded by the CMT + P welding technology is 1.4 times higher than that of the DP1000 dual-phase steel welded by the electron beam welding technology [ 15 ]. Because the CMT + P welding technology utilizes the arc as the heat source, it has the advantages of a stable welding arc, low heat input, and no spatter in the welding process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average tensile strength of the welded joints is 925 MPa under different welding parameters. The tensile strength of the dual-phase steel welded by the CMT + P welding technology is 1.4 times higher than that of the DP1000 dual-phase steel welded by the electron beam welding technology [ 15 ]. Because the CMT + P welding technology utilizes the arc as the heat source, it has the advantages of a stable welding arc, low heat input, and no spatter in the welding process.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the microhardness of the weldments varied from 221 HV to 243 HV. Sezgin et al [ 15 ] used electron beam welding technology to weld DP1000 dual-phase steel with 1.2 mm thickness. They found that the average tensile strength of the weldments was 656 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, numerous scholars have conducted studies on solder joints. Sezgin [19] examined the electron beam welding (EBW) method of TRIP 800 steel and DP 1000 steel and found through observation that the TRIP 800 joining absorbed more energy than the DP 1000 joining at impact notch experiment for each temperature. Emre [20] studied the impact imposed by the welding current and welding time on nugget shape, while conducting the tensile shear experiment on welding specimens in the meantime.…”
Section: Introductionmentioning
confidence: 99%